Governing Academic Medical Center Systems: Evaluating and Choosing Among Alternative Governance Approaches. (February 2018) - Chari, Ramya; O'Hanlon, Claire; Chen, Peggy; Leuschner, Kristin; Nelson, Christopher
Abstract : The ability of academic medical centers (AMCs) to fulfill their triple mission of patient care, medical education, and research is increasingly being threatened by rising financial pressures and resource constraints. Many AMCs are, therefore, looking to expand into academic medical systems, increasing their scale through consolidation or affiliation with other health care systems. As clinical operations grow, though, the need for effective governance becomes even more critical to ensure that the business of patient care does not compromise the rest of the triple mission. Multi-AMC systems, a model in which multiple AMCs are governed by a single body, pose a particular challenge in balancing unity with the needs of component AMCs, and therefore offer lessons for designing AMC governance approaches. This article describes the development and application of a set of criteria to evaluate governance options for one multi-AMC system—the University of California (UC) and its five AMCs. Based on a literature review and key informant interviews, the authors identified criteria for evaluating governance approaches (structures and processes), assessed current governance approaches using the criteria, identified alternative governance options, and assessed each option using the identified criteria. The assessment aided UC in streamlining governance operations to enhance their ability to respond efficiently to change and to act collectively. Although designed for UC and a multi-AMC model, the criteria may provide a systematic way for any AMC to assess the strengths and weaknesses of its governance approaches.